Produtos tópicos e orientações em radiodermatites: um estudo descritivo com mulheres com câncer de mama submetidas à radioterapia - Rocha, Annelise Arantes (2020)
Introduction: Cancer is the leading cause of death and one of the biggest health problems in the world. Among the most frequent acute adverse events in women with breast cancer (BC) in radiotherapy (RT) are skin reactions denominated radiodermatitis (RD). RD that can impair quality of life, cause discomfort and even interrupt the treatment. And to reduce the occurrence of RD, some skin care is adopted, which includes the use of topical products. Purpose: The focus of this study is to characterize the topical products used and the guidelines received by women with BC in RT to aim the prevention and management of RD. Methods: A prospective cohort study was carried in a university hospital with 100 women, over 18 years old and with non-metastatic BC. RDs were classified according to the Radiation Therapy Oncology Group scale and data were collected before the start of RT (T0) and during (T1, T2, T3, T4, T5). The guidelines received by the patients. Were recorded, as well as the topical products used in the irradiated area. The SPSS® software was used to perform descriptive analysis, measures of central tendency and dispersion for continuous variables and proportions for categorical data. Results: RD grade 3 and 4 was present from T3 and there was a gradual increase in RD grade 2 from T2. Considering the guidelines received by patients, a low percentage was (8%, n = 8) of patients who received verbal guidance regarding skin care was identified in order to manage and prevent DR, including the use of topical products, in T0, and only after treatment has started that the guidelines have increased. In relation to topical products, Canola Oil with Calendula was the most used in T1 (78.7%, n = 70) and T2 (79.6%, n = 78), the cold compress had a higher frequency of use in T3 (80.2 %, n = 73) and in T4 (79.6%, n = 74), Nystatin in T3 (67.0%, n = 61), T4 (74.2%, n = 69) and 1% Silver Sulfadiazine in T5 (41.3%, n = 33). Conclusion: We found a variety of topical products recommended, in particular Canola Oil with Calendula as prevention and 1% Silver Sulfadiazine as management of RD. Keywords: Radiodermatitis; Breast cancer; Radiotherapy; Prophylaxis; Treatment.